THU0634 Comparing preferences of patients with rheumatic diseases, of rheumatologists, nurses and pharmacists toward the treatment of rheumatic diseases with biological agents: results from the cara study. (15th June 2017) - Sarzi-Puttini, P; Cortesi, PA; Sinigaglia, L; Montecucco, CM; Giacomelli, R; Lapadula, G; Olivieri, I; Giardino, A; DIdoni, G; Scalone, L; Mantovani, LG; Mecchia, M; et al.
Abstract : Background: The management of patients with rheumatologic diseases (RDs) involves a complex interaction between different parties such as patients, physicians, pharmacists. The development of biologic therapies has created a more complex decision-making process to select the treatment option for patients. To optimize the appropriateness of the decisions, it is necessary to be informed and aware of the preferences of the interested parties. Objectives: To estimate preferences of relevant treatment characteristics with biological agents valued by the different subjects involved in the management of patients with rheumatic diseases. Methods: We involved patients with RDs, rheumatologists, nurses and pharmacists with experience in the treatment with/provision of biological drugs of these patients. Through a Discrete-Choice-Experiment, the participants valued 16 possible scenarios in which pairs of similarly effective treatments were described with 6 characteristics including 2–4 possible levels each: (1) frequency of administration; (2) mode and place of administration; (3) hospitality, service, efficiency and courtesy of health personnel; (4) frequency of reactions at the site of drug administration; (5) generalized undesired/allergic reactions; (6) additional cost: since the Italian NHS pays treatment costs, we included possible additional cost as monthly healthcare taxes for all the citizens, to make available the treatment to all target patients. relative importance of each characteristic was estimated through a random-effects conditional logistic regression model. Results: 513 patients, 110 rheumatologists, 51 nurses and 46 pharmacists from 30 centres through Italy participated. Characteristics (3), (4) and (6) were the most important for every subgroup, while (1) was the least important for patients and rheumatologists, (2) the least important for the pharmacists, (2) and (5) the least important for the nurses. The four subgroups were consistent in preferences towards the specified levels of characteristics (1) and (3) to (6). However, as for characteristic (2), pharmacists preferred autonomous subcutaneous injection with syringe, nurses preferred assisted infusion at an infusional center close to patient's place, patients and rheumatologists preferred autonomous subcutaneous injection with pen. Conclusions: Different subjects show different preferences for some treatment characteristics, which together with pure clinical aspects can play an important role in the choice and consequent success of treatments. Disclosure of Interest: P. Sarzi-Puttini: None declared, P. Cortesi Grant/research support from: Gilead, L. Sinigaglia: None declared, C. Montecucco: None declared, R. Giacomelli Grant/research support from: MSD, G. Lapadula: None declared, I. Olivieri: None declared, A. Giardino Employee of: MSD Italia, G. DIdoni Employee of: MSD Italia, L. Scalone: None declared, L. Mantovani: None declared, M. Mecchia Employee of: MSD Italia